Marx, Freud, fetiche, capitalismo e a religião iorubá - Dias, João Ferreira (Afro-Ásia, 2019)
Resenha de: MATORY, J. Lorand. The Fetish Revisited: Marx, Freud, and the Gods Black People Make. Durham: Duke University Press, 2018. 392p.